2019
DOI: 10.55374/jseamed.v3i1.43
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Clinical Efficacy of Platelet Rich Growth Factors (Prgf) in Managing Knee Osteoarthritis After Failed Conservative Treatment: Evidence From Real Practices

Abstract: Background:  Platelet rich growth factors (PRGF) comprise a biological treatment of knee osteoarthritis (OA).  Due to its limitation concerning the articular cartilage lesions’ healing potential, chondrocyte differentiation and external environment factors, clinical improvement of knee OA using PRGF treatment depends on preparation techniques. Objectives: The study aimed to demonstrate clinical outcomes of PRGF treatment in real practices. Methods: A prospective cohort study was conducted from Febr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…49/2019). The sample size was calculated based on a related study with an alpha of 0.05 and a power of 80% [18]. The calculated sample size was 524 knees divided into 424 knees in Kellgren and Lawrence (KL) grade I to III, and 100 knees in KL grade IV groups.…”
Section: Methodsmentioning
confidence: 99%
“…49/2019). The sample size was calculated based on a related study with an alpha of 0.05 and a power of 80% [18]. The calculated sample size was 524 knees divided into 424 knees in Kellgren and Lawrence (KL) grade I to III, and 100 knees in KL grade IV groups.…”
Section: Methodsmentioning
confidence: 99%
“…In 2019, Turajane et al performed a clinical trial investigating the efficacy of PRGF in knee OA patients who failed conservative treatment. Their results at 3 months follow-up showed that only 5.6% of patients with KL Grade 2-3 and 10.8% of patients with KL Grade 4 needed surgical intervention (38) . In 2020, Turajane et al performed another randomized, controlled trial comparing clinical outcomes of IA-platelet plasma concentrate and growth factors and intra-articular corticosteroid injections for the treatment of knee OA.…”
Section: Current Clinical Practice and Evidence-based Medicine In Tha...mentioning
confidence: 99%